Temporal resource partitioning of the flight activities of three bee species in East Java: Pembagian sumber daya temporal dari aktivitas terbang tiga spesies lebah di Jawa Timur - Shullia, Nurul Insani; Subchan, Wachju; Raffiudin, Rika; Atmowidi, Tri; Priawandiputra, Windra; Ariani, Nunik Sri; Pujiastuti; Dewi, Aisyah Nurlatifah; Sabella, Yurika Nur; Siffahk, Lutmitha Nisaul; Nisa, Weni Khoiru; Novidayanti, Aldea Anisyafera (Perhimpunan Entomologi Indonesia, 2024)
The dwarf honey bee Apis florea Fabricius, was successful coexistence with larger bees, Apis cerana Fabricius and Apis dorsata Fabricius in Bangalore, India. However, there is a lack of A. florea foraging behavior that shared the same plant resources with A. cerana and stingless bee Tetragonula laeviceps (Smith) in Indonesia. This study investigated the foraging activities of two honey bee species (A. florea and A. cerana) and the stingless bee T. laeviceps, which live sympatrically and also seek environmental factors that influence the foraging behavior of bees. The flight activity was recorded on the bee farm at Jombang Regency, East Java Province, from 06.00–16.00 hours for three consecutive days. Environmental factors of temperature, humidity, and light intensity in open and close to the nest areas were recorded. This study reported that A. florea started foraging activity at 09.00, while A. cerana and T. laeviceps started to forage earlier, at 06.00 in the morning. Therefore, the foraging activities of bees in East Java, revealed temporal resource partitioning, which confirmed the results of a previous study in Bangalore. The temperature and humidity mainly influenced the foraging activity of the three bee species (P<0,001). Temporal resource partitioning in A. florea suggests a foraging strategy that coexists with sympatric honeybees and stingless bees. The high flight activity of A. florea at midday suggests that this species can adapt to high temperatures. This result implies that A. florea could be a potential future pollinator in tropical regions facing the issue of a warming climate.